Fighting Disability Condition in Andrew Solomon’s Novel Far Away From Tree (2012) - Rahmat, Fikri; Anwar, Desvalini (Universitas Negeri Padang, 2021)
This article is about the analysis of a novel Far Away from Tree (2017) by Andrew Solomon. There are two keywords that need to be explained in this study: Fighting and disability condition. According to Merriam-Webster (2018) fight means to put effort as determined effort. While according to Merriam Webster Dictionary disability means a physical, mental, cognitive, or developmental condition that impairs, interferes with, or limits a person’s ability to engage in certain tasks or actions or participate in typical daily activities and interaction. According to Merriam Webster Dictionary condition means something essential to the appearance or occurrence of something else